A language test in Kannada for expression in children - HN, Kathyayani (Journal of All India Institute of Speech and Hearing)
In this study an attempt was made at language testing (expression of ’concepts ’) in Kannada in children. The testing material consisted of 30 picture cards, depicting daily activities. The cards were presented to 30 normal children (5-8 years in age range), 6 hearing impaired children and 2 mentally retarded children.